Analisis Mengurangi Loss Time Pada Proses Stamping Di Mesin AIDA 800 T Blanking di PT. XYZ - Rohman, Ibnu Nur; Setiawan, Reza; Gusniar, Iwan Nugraha (Universitas Nusantara PGRI Kediri, 2023)
In a production process optimization is needed to increase the productivity of production results. This research was conducted on the Aida 800T Blanking machine, based on the results of field observations made on the Aida 800T Blanking machine at PT. XYZ there is frequent losstime, this hinders the production process which results in reduced production targets. Losstime often occurs during a production process, the factors that often occur are the environment, humans, materials, and machines. The purpose of this study is to find out how much the cost is due to loss time. The methods used to perform losstime analysis are 5 why analysis, Pareto diagrams and fishbone diagrams to identify problems that often occur in the production process. From the results of the research, it was found that the costs incurred were Rp. 6,509,220. By performing a losstime analysis, there is a cost saving of 3,797,736 during one month of production, so that the method is successfully used with the end result of doing kaizen.